The Role Of Training And Development Strategy In Rais- ing The Efficiency Of Human Resource Performance For Business Organizations. An exploratory study for Zain Iraq - Ebrahem Ahmad, Othman; khaleel Ibrahim, Hakeem; Ahmed HusseinAil, Momen (Opción, 2019)
The aim of the research is to identify the role of the training and development strategy in raising the efficiency of the human resource performance in the Iraqi private communications sector, Zain Company as a model, and the re- search sample represented (64) respondents. To reach the goal of the research, a questionnaire prepared for this purpose was used. In this paper, appropriate statistical methods such as (Alpha Cronbach test, simple and multiple line- ar regression) were adopted. The results of the research found that there is a relationship and statistically significant effect of training and development strategy practices (employee development, training, leadership development, learning and knowledge acquisition) in improving the human resource, as well as that (Zane) pays close attention to the training process and the develop- ment of skills and decision-making capabilities Operational or semi-routine, through finding independent administrative units that carry out practices for human resource management strategies. Research recommendations empha- sized the importance of intensifying training and development programs and making them periodically and with strategic directions, in addition to giving freedom to exchange and transfer Alomat between the sections themselves, as well as encouraging learning programs in order to raise the knowledge of employees in the company (Zian).